2014
DOI: 10.1111/jhn.12201
|View full text |Cite
|
Sign up to set email alerts
|

Different measurements of waist circumference and sagittal abdominal diameter and their relationship with cardiometabolic risk factors in elderly men

Abstract: SAD measured at the midpoint between the iliac crests and WC measured at the narrowest waist showed the best relationships with cardiometabolic risk factors in elderly men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Studies comparing SAD protocols suggest, however, that the NHANES protocol for SAD may be the most appropriate for identifying health risks [46,47]. A very similar protocol for SAD measurement was used successfully in a nationwide survey of over 6000 Finnish adults in 2000–2001 [48].…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing SAD protocols suggest, however, that the NHANES protocol for SAD may be the most appropriate for identifying health risks [46,47]. A very similar protocol for SAD measurement was used successfully in a nationwide survey of over 6000 Finnish adults in 2000–2001 [48].…”
Section: Discussionmentioning
confidence: 99%
“…Sagittal abdominal diameter has been proposed as a better marker of abdominal visceral adiposity than waist circumference with validation studies comparing SAD to imaging techniques demonstrating correlation coefficients between 0.724 and 0.804 (Kullberg et al ., ; Yim et al ., ). Studies undertaken in populations differing in ethnicity, age and BMI have identified SAD as a better predictor of cardiovascular, metabolic risk (Valsamakis et al ., ; Kullberg et al ., ; Risérus et al ., ; Yim et al ., ; Gletsu‐Miller et al ., ; Anunciação et al ., ), although this has not yet been evaluated by systematic review. Cut‐off values for predicting elevated cardiovascular risk have been proposed (Table ) and further work is required to establish prognostically useful values in more diverse populations.…”
Section: Trunk Circumferences and Diametermentioning
confidence: 99%
“…The sample size was calculated considering 4.3% as the frequency of MS observed in a previous study 12 , an acceptable range of variation of 5% and 95% as the alpha risk, resulting in a minimum sample of 62 elderly men. Exclusion criteria were: previous coronary events and use of medications that could interfere with glucose homeostasis, blood pressure and/or lipid metabolism.…”
Section: Methodsmentioning
confidence: 99%